Analisis Minat Mahasiswa Universitas Islam Negeri Antasari Banjarmasin dalam Berinvestasi di Pasar Modal - Mujahid Muhajid; Noor Sari; Muhammad Noval (At-Taradhi Jurnal Studi Ekonomi, 2020)
The purpose of this research was to determine the factors that influence the interest of FEBI UIN Antasari students for invest on the capital market, and to find out the perspectives of academics and practitioners on how to develop investment among students. The population in this study were 428 students of FEBI UIN Antasari who had become investors with a sample size of 81 students who were obtained using the Slovin formula with a standard error of 10%, as well as additional data that were analyzed qualitatively using 3 academics and 2 practitioners in the capital market. The data were processed using quantitative and qualitative methods of analysis that adapts to the conditions in the field that generate a response to the problems studied. The results explain the more dominant factors that cause students to be interested in investing in the capital market, namely motivation, followed by the risk recognition, learning, perception, income and learning factors. As well as the suggestions and opinions of academics and practitioners on how to increase the interest in investing in the stock market by the students is to increase human resources in the campus, increased support facilities, apply learning theory direct practice and the existence of the program or policy made by the leadership of the campus in increasing interest students invest in the capital market.Tujuan penelitian ini adalah untuk mengetahui faktor yang mempengaruhi minat mahasiswa FEBI UIN Antasari terhadap investasi di pasar modal, dan mengetahui perspektif akademisi dan praktisi tentang cara pengembangan investasi di kalangan mahasiswa. Populasi dalam penelitian ini adalah mahasiwa FEBI UIN Antasari yang sudah menjadi investor berjumlah 428 orang mahasiswa dengan jumlah sampel sebanyak 81 orang mahasiswa yang didapatkan dengan menggunakan rumus slovin dengan standar error 10%, serta tambahan data yang dianalisis secara kualitatif dengan menggunakan 3 orang akademisi dan 2 orang praktisi di pasar modal. Data diolah secara kuantitatif dan kualitatif sesuai karakteristik kedua rumusan. Hasil riset menunjukkan bahwa faktor yang lebih dominan penyebab mahasiswa berminat untuk melakukan investasi di Pasar Modal yaitu Motivasi, kemudian diikuti oleh faktor Pengenalan Risiko, Pembelajaran, Persepsi, Pendapatan dan Pembelajaran. Adapun saran dari akademisi dan praktisi untuk meningkatkan minat mahasiswa berinvestasi di pasar modal yaitu dengan meningkatkan sumber daya manusia di kampus, memperbanyak fasilitas pendukung, menerapkan pembelajaran teori praktik langsung serta adanya program ataupun kebijakan yang dibuat oleh pimpinan kampus dalam meningkatkan minat mahasiswa berinvestasi di pasar modal.